ISLAMIC LEADERSHIP AND HYBRID ECONOMIC ECOSYSTEM FOR SUSTAINABLE PESANTREN-BASED RELIGIOUS TOURISM DEVELOPMENT IN INDONESIA - Fathul Bari; Rahmatullah; Ahmad Naweed Rahimi khamosh; Ouail Brahim Sabri; Moh. Nadhif (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study analyzes how Islamic leadership shapes a hybrid economic ecosystem in sustainable pesantren-based religious tourism. Pesantren are usually examined as educational and religious institutions, while their role as integrated economic actors remains less developed in current scholarship. This research addresses that gap by examining Pondok Pesantren An-Nur II Al-Murtadlo, Malang, Indonesia, as a single qualitative case. Data were collected through in-depth interviews, participant observation, and institutional document analysis during six months of fieldwork from January to June 2025. The findings show that the pesantren builds economic sustainability through five connected elements: Islamic values, kyai-led governance, multi-sector business integration, resource-sharing mechanisms, and community-oriented tourism outcomes. Cooperatives, transportation services, fuel station operations, educational services, and tourism facilities function as interdependent units rather than separate businesses. This integration supports cross-subsidization, strengthens institutional resilience, and expands community participation. The study proposes the Pesantren Hybrid Islamic Economic Ecosystem model as a conceptual contribution to Islamic economics, social enterprise, institutional governance, and religious tourism studies. The model shows that faith-based institutions can pursue economic resilience without weakening religious, educational, and social missions Keywords: Hybrid Economy; Islamic Economic Ecosystem; Islamic Leadership; Pesantren; Religious Tourism. Abstrak Penelitian ini menganalisis peran kepemimpinan Islam dalam membentuk ekosistem ekonomi hibrida pada pengembangan wisata religi berbasis pesantren yang berkelanjutan. Selama ini pesantren lebih sering dikaji sebagai lembaga pendidikan dan keagamaan, sedangkan perannya sebagai aktor ekonomi terintegrasi belum banyak dijelaskan secara sistematis. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus tunggal di Pondok Pesantren An-Nur II Al-Murtadlo, Malang, Indonesia. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen kelembagaan selama enam bulan, dari Januari hingga Juni 2025. Temuan menunjukkan bahwa keberlanjutan ekonomi pesantren dibangun melalui lima unsur yang saling terkait, yaitu nilai-nilai Islam, tata kelola berbasis kepemimpinan kyai, integrasi unit usaha multisektor, mekanisme berbagi sumber daya, serta luaran wisata yang berorientasi pada masyarakat. Koperasi, transportasi, SPBU, layanan pendidikan, dan fasilitas wisata berfungsi sebagai unit yang saling menopang. Integrasi tersebut mendukung subsidi silang, memperkuat ketahanan kelembagaan, dan memperluas partisipasi masyarakat. Penelitian ini menawarkan model Pesantren Hybrid Islamic Economic Ecosystem sebagai kontribusi bagi kajian ekonomi Islam, kewirausahaan sosial, tata kelola kelembagaan, dan wisata religi. Kata kunci: ekonomi hibrida; ekosistem ekonomi Islam; kepemimpinan Islam; pesantren; wisata religi